2020
DOI: 10.1186/s12891-020-03483-z
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and clinicians’ perspectives on a ‘fast-track’ pathway for patients with sciatica in primary care: qualitative findings from the SCOPiC stratified care trial

Abstract: Background: Sciatica is common and associated with significant impacts for the individual and society. The SCOPiC randomised controlled trial (RCT) (trial registration: ISRCTN75449581) tested stratified primary care for sciatica by subgrouping patients into one of three groups based on prognostic and clinical indicators. Patients in one group were 'fast-tracked' for a magnetic resonance imaging (MRI) scan and spinal specialist opinion. This paper reports qualitative research exploring patients' and clinicians'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…A total of 993 studies were identified through database searching, of which 23 studies were [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] included for qualitative synthesis, with a total of 451 patients (271 were female, 180 male). See Supplementary Material File S1 Table S1 for details of the excluded articles and the demographics for the included studies and Supplementary Material File S1 Table S2 for detailed data extraction tables.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 993 studies were identified through database searching, of which 23 studies were [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] included for qualitative synthesis, with a total of 451 patients (271 were female, 180 male). See Supplementary Material File S1 Table S1 for details of the excluded articles and the demographics for the included studies and Supplementary Material File S1 Table S2 for detailed data extraction tables.…”
Section: Resultsmentioning
confidence: 99%
“…The number of other allied health care professionals could not be obtained from the manuscripts. A total of 8 studies [ 23 , 24 , 25 , 26 , 30 , 32 , 34 , 35 ] focused on physician encounters. A total of seven studies focused on physiotherapist interactions within interventions [ 27 , 31 , 37 , 39 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…There is a wealth of literature on the development of theory-informed interventions that aim to change clinician behaviour, with varying results (see, for instance: [24][25][26][27]). Much of this literature focuses on development of behaviour change interventions themselves, and on evaluating clinicians' and patients' uptake and engagement [28][29][30]; and this research has highlighted some similar challenges to those identified here, including the practical and time issues involved in engaging clinicians, and the challenge of achieving clinician 'buy in' . There has been a lack of focus in the literature, however, on specifically developing the clinician support to enable successful delivery of interventions in RCTs, as reported here, which we argue is a crucial element of intervention development that is often overlooked.…”
Section: Discussionmentioning
confidence: 86%
“…Following removal of duplicates and application of inclusion/exclusion criteria, 27 full text published papers and one service evaluation report were included in the final analysis. Three publications related to the same research study [16][17][18], including a Health Technology Assessment (HTA) report [16], RCT [17] and a qualitative study [18].…”
Section: Literature Searchmentioning
confidence: 99%